Intraindividual relations between achievement goals and discrete achievement emotions: An experience sampling approach. (February 2016) - Goetz, Thomas; Sticca, Fabio; Pekrun, Reinhard; Murayama, Kou; Elliot, Andrew J.
Abstract: Theories on the link between achievement goals and achievement emotions focus on their within-person functional relationship (i.e., intraindividual relations). However, empirical studies have failed to analyze these intraindividual relations and have instead examined between-person covariation of the two constructs (i.e., interindividual relations). Aiming to better connect theory and empirical research, the present study ( N = 120 10th grade students) analyzed intraindividual relations by assessing students' state goals and emotions using experience sampling ( N = 1409 assessments within persons). In order to replicate previous findings on interindividual relations, students' trait goals and emotions were assessed using self-report questionnaires. Despite being statistically independent, both types of relations were consistent with theoretical expectations, as shown by multi-level modeling: Mastery goals were positive predictors of enjoyment and negative predictors of boredom and anger; performance-approach goals were positive predictors of pride; and performance-avoidance goals were positive predictors of anxiety and shame. Reasons for the convergence of intra- and interindividual findings, directions for future research, and implications for educational practice are discussed. Highlights: Theories in the behavioral sciences commonly focus on intraindividual functioning. However, empirical studies have typically focused on interindividual variation. We analyzed both intra- and interindividual relations between achievement goals and emotions. The intraindividual relations were similar to the interindividual relations. Both intra- and interindividual relations were consistent with theoretical expectations.